Enhancing Logical Thinking in Preschoolers: The Educational Block Media Approach - Kurniawati, Febriana; Surifah, Jamilatus; Tohani, Entoh; Rolina, Nelva (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
The capacity for logical thinking is crucial in early childhood development, facilitating the ability to reason and analyze from multiple perspectives to form concrete conclusions. This study investigates the effect of educational block media on enhancing logical thinking abilities among preschool children aged 4-5 years. Employing a quasi-experimental design with a pretest-posttest control group format, the research aims to evaluate the effectiveness of these tools in an educational setting. Forty children from a kindergarten class were chosen through purposive sampling as the study's participants. The data collection involved administering performance tests, both before and after the introduction of the educational blocks, to assess the children's logical thinking skills quantitatively. Statistical analysis was performed using SPSS 21, which included tests for Normality, Homogeneity, and the Independent Sample t-test to compare the experimental and control groups' scores. The results showed that the experimental group, which used the educational block media, significantly outperformed the control group in the posttest, with mean scores of 15.65 and 9.90, respectively. The statistical analysis supported these results with a t-test yielding a significance level of 0.000, confirming the positive impact of the educational blocks on the development of logical thinking skills. The findings highlight the effectiveness of using tangible educational tools like blocks in stimulating cognitive processes among young children. This study provides valuable implications for early childhood education practices, recommending integrating educational block media into teaching strategies to enhance cognitive development. It also suggests areas for further research, particularly in the longitudinal impact of such educational interventions on child development over time.